Determinación de los niveles de nitrógeno ureico en la sangre y leche en vacas y su influencia en la producción y reproducción - Naranjo Trujillo, Lenny Victoria (2025)
The determination and evaluation of blood urea nitrogen (BUN) and milk urea nitrogen (MUN) is an important and recommended practice to know the nutritional status, feed quality and its relationship with the productive performance of milk, days of lactation and reproductive effectiveness of cows. The present study was carried out in the Capito community of the parish of San Simón, in the Guaranda canton, Bolívar province, with the objective of determining the levels of urea nitrogen in blood and milk in cows and its influence on production and reproduction. As well as knowing the levels of urea nitrogen through the colorimetric enzymatic technique, establishing the productive and reproductive parameters and identifying the relationship in blood and milk urea nitrogen with the production and reproduction parameters. Therefore, the determination of the BUN and MUN levels in female cattle in the Capito community will allow improving the efficiency in terms of the feed provided to cattle, preventing metabolic diseases that can affect the milk production and reproduction of these animals. Once the results were obtained, they were analyzed using the Pearson and Spearman correlation test together with descriptive statistics. In this way, it was established that 1.67% and 3.33% of the cows evaluated presented high levels of urea in milk (≥18 mg/dL) and blood (≥20 mg/dL), on the other hand, 76.6% and 73.33% of the same animals presented levels below the range of NUS (≤10 mg/dL) and NUL (≤12 mg/dL). Regarding the productive and reproductive variables, the cows were between the second (>100 days) and third third (>200 days) of milk production and presented low milk production (≤10 Lt) per day along with low levels of milk urea. A high positive correlation could not be established between the reproductive and productive variables between NUS and NUL.